Attenuation of antigen-specific T helper 1 immunity by Neolitsea hiiranensis and its derived terpenoids - Yin-Hua Cheng; Ih-Sheng Chen; Ying-Chi Lin; Chun-Wei Tung; Hsun-Shuo Chang; Chia-Chi Wang (PeerJ, 2016)
Background T cells play a pivotal role in the adaptive immunity that participates in a wide range of immune responses through a complicated cytokine network. Imbalance of T-cell responses is involved in several immune disorders. Neolitsea species, one of the biggest genera in the family Lauraceae, have been employed widely as folk medicines for a long time in Asia. Previous phytochemical investigations revealed the abundance of terpenes in the leaves of N. hiiranensis, an endemic Neolitsea in Taiwan, and demonstrated anti-inflammatory activities. However, the effect of N. hiiranensis on the functionality of immune cells, especially T cells, is still unclear. In this study, we utilize in vitro and in vivo approaches to characterize the effects of leaves of N. hiiranensis and its terpenoids on adaptive immune responses. Methods Dried leaves of N. hiiranensis were extracted three times with cold methanol to prepare crude extracts and to isolate its secondary metabolites. The ovalbumin (OVA)-sensitized BALB/c mice were administrated with N. hiiranensis extracts (5–20 mg/kg). The serum and splenocytes of treated mice were collected to evaluate the immunomodulatory effects of N. hiiranensis on the production of OVA-specific antibodies and cytokines. To further identify the N. hiiranensis-derived compounds with immunomodulatory potentials, OVA-primed splenocytes were treated with compounds isolated from N. hiiranensis by determining the cell viability, cytokine productions, and mRNA expression in the presence of OVA in vitro. Results Crude extracts of leaves of N. hiiranensis significantly inhibited IL-12, IFN-γ, and IL-2 cytokine productions as well as the serum levels of antigen-specific IgM and IgG2a in vivo. Two of fourteen selected terpenoids and one diterpenoid derived from the leaves of N. hiiranensis suppressed IFN-γ in vitro. In addition, β-caryophyllene oxide attenuated the expression of IFN-γ, T-bet, and IL-12Rβ2 in a dose-dependent manner. N. hiiranensis-derived β-caryophyllene oxide inhibited several aspects of adaptive immune responses, including T-cell differentiation, IFN-γ production, and Th1-assocaited genes. Conclusion As IFN-γ is the key cytokine secreted by T helper-1 cells and plays a pivotal role in Th1 immune responses, our results suggested that the N. hiiranensis and its terpenoids may possess potential therapeutic effects on Th1-mediated immune disorders.